Determinants of Intra-industry Trade between Western Balkans and EU-15: Evidence from Bilateral Data - Valerija Botrić (International Journal of Economic Sciences and Applied Research, 2013)
This paper provides analysis of intra-industry trade determinants between Western Balkan countries and old European Union Member States. Overall intra-industry trade has been analysed, as well as its horizontal and vertical component, within bilateral trade framework. All components of intra-industry trade exhibit much lower degree than EU New Member States achieved during their accession period. Most of the intra-industry trade is related to vertical component, while horizontal component is negligible. Intra-industry trade determinants analysis has revealed that relative income level, distance, relative factor endowments and relative trading costs are significant factors for the analysed countries' trade relations. The determinants of vertical component are the same, although for some variables smaller significance levels were found. Horizontal component determinants in general have the same sign, although relative income levels, employment shares and export costs were not found significant.
Keywords: F14; F15; 330; intra-industry trade; vertical intra-industry trade; horizontal intra-industry trade; Western Balkans; EU accession